Misi Kristen di Indonesia: Kesaksian Kristen Protestan - Benyamin Fleming Intan (Reformed Center for Religion and Society, 2015)
ABSTRACT: In this article, the writer reveals the presence and struggles of Protestant churches in Indonesia doing God's mission within world's largest Muslim population country. Firstly, the writer explains the challenges and strives of Protestant churches since the time of Dutch colonialism, Japanese colonization, until Indonesian independence which includes the Old Order and the New Order. This article also highlights Indonesian churches’ struggle of independence to release themselves from the control of Dutch government, fully leaning to Christ, as well as the strategic role of Christianity in preventing nation’s disintegration to make Indonesia one. After that, the writer then performs critical reflection on the struggles of Protestant churches in Indonesia from the perspective of Reformed theology. The writer found that the presence of Christian mission in Indonesia is far from the force of arms and economic greed. However, churches in Indonesia cannot detach themselves from various challenges and suffering in God's mission which includes Evangelical Mandate and Cultural Mandate. Therefore, while they are still entrusted by Christ, churches in Indonesia ought to perform their dutiful calling faithfully and joyfully. KEYWORDS: God's mission, witness, evangelism, protestant church in Indonesia, ideology, religion-state relation, mission's institution